Assessing Heavy Metal Contamination in Traditional Herbal Medicine (Jamu) by Atomic Absorption Spectrophotometry - Mahmudi Mahmudi; Mutiara Annisa; Mutia Farida; Muhammad Yusuf; Saiful Azhari; Yunda Fachrunniza (Graha Primera Saintifika, 2023)
Heavy metal contamination of traditional herbal medicine (jamu) is a threat to humans, especially at levels above known threshold concentrations. Traditional herbal medicine found in Banda Aceh City – Indonesia, polluted by heavy metals cadmium (Cd), lead (Pb), and mercury (Hg) was performed. Heavy metal analysis used Flame - Atomic Absorption Spectrometry (FAAS) and Chemical Vapor Generation - Atomic Absorption Spectrometry (CVG - AAS) methods. The validation of the method was performed to obtain more accurate heavy metal analysis results for the samples. Heavy metal contamination, especially Pb metal, with concentrations of 4.32 ± 0.14 mg/Kg to 29.25 ± 0.24 mg/Kg. The Cd metal contamination was only found in herbal medicine sample E with a concentration of 0.80 ± 0.02 mg/Kg, above the threshold. The Hg metal contamination was also found with concentrations of 0.20 ± 0.01 to 2.14 ± 0.06 mg/Kg, and some were not detected. The government should be very concerned about stopping the distribution of herbal medicine that can be harmful to health and should inspect drug stores that still sell herbs that do not have established standards.